COMMUNITY STRUCTURE ECHINODERMS (ASTEROIDEA, OPHIUROIDEA, ECHINOIDEA AND HOLOTHUROIDEA) IN THE MARINE NATIONAL PARK EAST SULAWESI WAKATOBI - Eddy Yusron (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
A study on Echinoderms community structure in marine national parks of Wakatobi, Southeast Sulawesi was conducted in six locations, i.e., Waha Beach, Coastal Sombo, Beach Houses, Beach Kapota, Banakawa beach, and Umala beach in October 2013. All of the six parks were located the Wakatobi territorial waters with coordinates of 5°06'25